“Aria di Ricerca in Valle del Serchio”: a cross-sectional citizen science study to evaluate CKD prevalence and associations with environmental risk factors in the Serchio Valley (Lucca, Tuscany, Italy) - Doccioli, Chiara; Sera, Francesco; Stoppa, Giorgia; De Marchi, Bruna; Catelan, Dolores; Ficorilli, Antonella; Malavasi, Giulia; Biggeri, Annibale (Frontiers in Public Health, 2025)
BackgroundChronic kidney disease (CKD) represents a growing global public health issue, with an estimated prevalence of around 11% in the most developed countries. This study, conducted as part of the European project CitieS-Health, aimed to estimate the prevalence of CKD in the Serchio Valley, Tuscany, Italy, an area subject to environmental contamination from various sources, including a potentially polluting copper foundry.MethodsThis cross-sectional study was conducted from 2019 to 2022 among a representative sample of 400 adults from eight municipalities, integrating a citizen science (CS) approach to enhance public engagement. The study aimed to estimate the prevalence of CKD in the area, as assessed by the decrease of estimated Glomerular Filtration Rate (eGFR). Data on lifestyle, clinical parameters, and environmental exposures were collected, employing a standardized protocol developed by the Disadvantaged Populations eGFR Epidemiology Study (DEGREE). The eGFR was calculated using three equations: CKD-EPI 2009, Modification of Diet in Renal Disease (MDRD), and CKD-EPI 2021. Associations between risk factors and CKD were examined through multivariate analyses.ResultsResults revealed a CKD prevalence of 12.7% using the CKD-EPI 2009 formula, 15.8% with the MDRD equation, and 10.5% according to the CKD-2021 definition, with age, hypertension, and diabetes being significant risk factors. These estimates are significantly higher than the national average reported in Italian studies (6–9%). Moreover, residential proximity to (< 2 km) and employment in the copper foundry resulted associated with eGFR reduction (OR = 1.36; 90%CI = 0.80, 2.29 and OR = 2.14; 90%CI = 0.89, 5.13, respectively; estimated with ordinal logistic regression, CKD defined per 2021 criteria).ConclusionIn conclusion, the study revealed an increased prevalence of CKD in an area affected by heavy metal pollution, particularly cadmium. These findings underscore the impact of environmental exposures on kidney health, emphasizing the need for targeted interventions and public health measures to mitigate CKD prevalence in pollution-exposed communities.